“What do I wish I had known? Don't expect the road to be full of flowers”: Advice from female STEM leaders in the GCC countries to younger women working in STEM fields - Martina Dickson; Maram Alharthi (Social Sciences and Humanities Open)
Many countries, including those in the Gulf Cooperation Council (GCC) countries, have been extremely successful in achieving gender equity in university level STEM programs, but problems of inequity persist further along STEM career trajectories. In GCC countries, there is a lot of governmental support for women, who are supported with facilitative policies and practices to ensure representation of nationals in the workplace, including their prioritisation for employment over expatriates. However, there remains a large gender gap in positions of leadership in STEM fields, which would appear to be at odds with the positive statistics for girls' STEM performance compared to boys' in schools, and at odds with the fact that female university graduates outnumber male graduates in higher education in all GCC countries, often including in STEM courses. In this study, fifteen GCC citizen women working in leadership positions in STEM fields - both in industrial/commerce and academic settings - participated in one to one, in-depth focused interviews. They reflected on the advice they would give to younger female counterparts embarking upon STEM careers. The study aimed to better understand the factors enabling their career journeys, success factors and barriers which they faced, in order to be able to provide recommendations. These were curated through a frame of giving advice to younger women interested in pursuing STEM careers. The key themes of the interviews included advice to cultivate personal qualities including kindness and honesty, to gain work experience ‘in the trenches’ before aspiring to leadership roles, build up personal resilience and perseverance including in the face of gender bias, listen to one's own intuition and to choose a spouse as wisely as possible. There was contradictory advice as to whether or not to share one's achievements publicly.